The advertisement call of the toad Rhinella humboldti (Bufonidae) - Torres-Suárez, Olga Lucía; Vargas-Salinas, Fernando (Zootaxa, 2013)
Despite important advances in understanding phylogenetic relationships among anurans (Frost et al. 2006; Pyron & Wiens, 2011), many uncertainties persist regarding phylogenetic affinities and taxonomic limits. The male advertisement call offers numerous opportunities to find diagnostic characters and is therefore useful for anuran species delimitation (Gerhardt & Huber, 2002; Grant et al. 2006). Thirteen species are recognized within the Rhinella granulosa group (Narvaes & Rodrigues, 2009; Sanabria et al. 2010) although it is possible that R. dorbignyi and R. fernandezae being conspecifics (Guerra et al. 2011, page 36). The advertisement call has been described for nine species of the granulosa group: Rhinella granulosa, R. bergi, R. major, R. azarai, R. fernandezae, R. dorbignyi, R. merianae, R. centralis and R. pygmaea (Köhler et al. 1997; Guerra et al. 2011; São-Pedro et al. 2011; Ribeiro de Carvalho et al. 2013). Some information regarding call features are available for R. humboldti from populations of Guyana (Lescure & Marty, 2000); however, there are no associated data of male body size, sample size, and call traits such as pulse number per notes, note duration, etc. Here we provide a formal description of the advertisement call of R. humboldti using call recordings obtained in a population in Colombia, South America.